2017
DOI: 10.1016/j.brat.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The behavioral economics of social anxiety disorder reveal a robust effect for interpersonal traits

Abstract: Recent evidence suggests that reduced generosity among individuals with social anxiety disorder (SAD) in behavioral economic tasks may result from constraint in changing behavior according to interpersonal contingencies. That is, people with SAD may be slower to be more generous when the situation warrants. Conversely, more global effects on generosity may be related to interpersonal vindictiveness, a dimension only somewhat related to SAD. A total of 133 participants, 73 with the generalized form of SAD, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
2
8
1
Order By: Relevance
“…These findings conflict with those from our earlier studies using the same iPD task, in which anxious/ depressed youths engaged in more cooperative behavior in response to coplayer defection than did nondiagnosed peers (e.g., McClure et al, 2007;McClure-Tone et al, 2011). However, they align with research that has yielded evidence of a cold and withholding style, marked by failure to reciprocate positive social behaviors, among some individuals with high social anxiety during economic exchange games (e.g., Rodebaugh et al, 2016;Rodebaugh et al, 2011;Rodebaugh et al, 2013;Rodebaugh et al, 2017). Thus, rather than predicting an atypical pattern of responding to others' negative behaviors with putative bids for conciliation, social anxiety appeared, in this sample, to predict a tendency to respond atypically-and aversively-to positive behavior from others.…”
Section: Hypothesis 3: Effects Of Social Anxiety On Playcontrasting
confidence: 98%
See 2 more Smart Citations
“…These findings conflict with those from our earlier studies using the same iPD task, in which anxious/ depressed youths engaged in more cooperative behavior in response to coplayer defection than did nondiagnosed peers (e.g., McClure et al, 2007;McClure-Tone et al, 2011). However, they align with research that has yielded evidence of a cold and withholding style, marked by failure to reciprocate positive social behaviors, among some individuals with high social anxiety during economic exchange games (e.g., Rodebaugh et al, 2016;Rodebaugh et al, 2011;Rodebaugh et al, 2013;Rodebaugh et al, 2017). Thus, rather than predicting an atypical pattern of responding to others' negative behaviors with putative bids for conciliation, social anxiety appeared, in this sample, to predict a tendency to respond atypically-and aversively-to positive behavior from others.…”
Section: Hypothesis 3: Effects Of Social Anxiety On Playcontrasting
confidence: 98%
“…Moreover, interpersonal constraint was observed both in general and following the coplayer's defection, which suggests that it did not exclusively constitute a response to perceived betrayal or rejection. Notably, in subsequent research from this group, findings indicated that several characteristics, particularly vindictiveness or a lack of empathy, better predicted interpersonal constraint than did SAD (Rodebaugh, Heimberg, Taylor, & Lenze, 2016;Rodebaugh et al, 2017).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Cooperation may be more affected by other symptoms than by anxiety itself: patients with GSAD gave less than controls in a Prisoner’s Dilemma [52], but giving was more strongly associated with quality of friendships and the interpersonal traits of vindictiveness and coldness than by the diagnosis [52, 53]. In students with attachment anxiety, symptoms of anxiety and avoidance did not significantly predict cooperation, but highly anxious patients were slower to make decisions and less consistent in their performance on the Assurance Game but not the Prisoner’s Dilemma, indicating a chronic lack of trust, since the Assurance Game is a version of the Prisoner’s Dilemma that encourages cooperation by giving the highest payoff when both players cooperate.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Kashdan and Steger (2006) found diminished positive experiences and diminished intensity of positive emotions among high compared with low socially anxious individuals. Finally, Rodebaugh and colleagues (2017) found that increases in generosity toward known compared with unknown individuals demonstrated by individuals without SAD was attenuated among individuals with SAD. Likewise, our findings suggest that positive processes occurring among NSA individuals (enhancement of synchrony in closeness-generating conversations) are not found among individuals with SAD.…”
Section: Discussionmentioning
confidence: 91%